Ocular Redness – II: Progress in Development of Therapeutics for the Management of Conjunctival Hyperemia - Singh, Rohan Bir (Ocul Surf, 2021)
Conjunctival hyperemia is one of the most common causes for visits to primary care physicians, optometrists, ophthalmologists, and emergency rooms. Despite its high incidence, the treatment options for patients with conjunctival hyperemia are restricted to over-the-counter drugs that provide symptomatic relief due to short duration of action, tachyphylaxis and rebound redness. As our understanding of the immunopathological pathways causing conjunctival hyperemia expands, newer therapeutic targets are being discovered. These insights have also contributed to the development of animal models for mimicking the pathogenic changes in microvasculature causing hyperemia. Furthermore, this progress has catalyzed the development of novel therapeutics that provide efficacious, long-term relief from conjunctival hyperemia with minimal adverse effects.